Pipeline Reliability Assessment For Interacting Corrosion Defect - Kishor, Ricknesh (IRC, 2015)
Pipelines have been the most practical method to transport oil and gas in the industry. However, as the structure operates with time, it is exposed to many types of defects. One of the major threats to offshore pipelines has been corrosion. Corrosion deteriorates the integrity and structural strength of pipeline. This research derived corrosion distributions based on interacting defect models and used them to perform reliability analysis of pipelines. The existing interacting models that are applied are obtained from American Society of Mechanical Engineers (ASME), Det Norske Veritas (DNV) and Pipeline Operators Forum (POF). Comparing the results of these analysis showed that considering the depth, length and width of corrosion is critical to pipeline failure modeling and reliability estimations. This research aims at assessing the reliability of pipelines with corrosion defects subjected to interacting defect using the probabilistic approaches. The softwares used are BestFit and Variables Processor (VaP) to obatain the pipeline’s probability of failure. A sensitivity analysis is performed for different levels of corrosion damage to identify the influence of the various parameters in the probability of burst collapse of corroded and intact pipes. The results of the reliability, sensitivity and uncertainty analysis are compared with results obtained among codes currently used in practice.